2017
DOI: 10.1002/cbdv.201700270
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Volatile Emission in Rhus coriaria Organs During Different Stages of Growth and Evaluation of the Essential Oil Composition

Abstract: Rhus coriaria, also known as Sumac, has been traditionally used in many countries as spice, condiment, dying agent, and medicinal herb. The chemical composition of essential oils (EOs) and the volatile emissions from different organs of this species collected in Sicily (Italy) were analyzed by gas chromatography-flame ionization detection and gas chromatography/mass spectrometry. Monoterpene and sesquiterpene hydrocarbons were the most abundant class in the volatile emissions with β-caryophyllene and α-pinene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…This variation is exemplified in higher furfural and nonanal levels in roasted samples. Likewise, previous reports (Bahar & Altug 2009;Giovanelli et al 2017;Morshedloo et al 2018;Reidel et al 2017) on fresh sumac fruit analyzed using SPME from Turkey, Italy and Iran reported for furfural and nonanal presence at trace levels, suggesting that these are key markers indicative of the roasting process.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This variation is exemplified in higher furfural and nonanal levels in roasted samples. Likewise, previous reports (Bahar & Altug 2009;Giovanelli et al 2017;Morshedloo et al 2018;Reidel et al 2017) on fresh sumac fruit analyzed using SPME from Turkey, Italy and Iran reported for furfural and nonanal presence at trace levels, suggesting that these are key markers indicative of the roasting process.…”
Section: Discussionsupporting
confidence: 67%
“…Abundance of monoterpenes has been reported in sumac fruit grown in Italy (Giovanelli et al 2017;Reidel et al 2017), with α-pinene, β-ocimene and fenchone as the main components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Italy, the VOCs emitted from the different organs of Sicilian R. coriaria at different growth stages, extracted by Solid Phase Micro‐Extraction (SPME) and analyzed by GC/MS were reported. Results clearly indicated the predominance of monoterpenes and sesquiterpenes, represented mainly by pinene isomers ( α and β ) in addition to β ‐caryophyllene.…”
Section: Phytochemical Studiesmentioning
confidence: 99%
“…Sumac’s name is derived from ‘sumaga’, which simply means red in the Syrian language ( Shabbir, 2012 ). Sumac has been traditionally used in many Middle Eastern and Mediterranean countries as a spice, dying agent, and medicinal herb ( Reidel et al, 2017 ). It is widely used as a condiment in Turkey and Iran to enhance the taste of poultry and vegetable dishes ( Ravindran, Pillai & Divakaran, 2012 ).…”
Section: Introductionmentioning
confidence: 99%